Pameran kaligrafi kontemporer sebagai media pembelajaran tipografi di Nusa Pustaka Kabupaten Polewali Mandar - Nurabdiansyah Nurabdiansyah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This program was an effort to introduce thetypography to the public through an exhibition of calligraphy.The combination of typography and Islam producesmonumental works that we often find in the form ofcalligraphy. Typographic acculturation with Arabic letters isthen known more widely through calligraphy works which arefound in monumental artifacts in the form of places ofworship, buildings to tombs. This exhibition took place inNusa Pustaka, Pambusuang Village, an area that is familiarwith the calligraphy in Polewali Mandar District. Thetypography science component that is understood by thepeople in the previous Pambusuang Village is theclassification of letter characters in calligraphy known as Khat.In a typographic perspective, the development of calligraphytoday is not limited to khat-khat as we commonly have known.It can be developed into contemporary calligraphy. In carryingout this Community Service program, the works ofcontemporary calligraphy chosen for display were the worksof Aziz Ahmad. Aziz Ahmad's calligraphy works are differentfrom the calligraphy grips that we have seen previously. AzizAhmad's calligraphy works combine drawings with Arabicletter calligraphy. By displaying Azis Ahmad's work, thecommunity was invited to recognize different letter characterswith calligraphy grips, as well as to introduce typography tothe public through observing the character of letters in thepresented calligraphy works.